High-frequency (>50 MHz) medical ultrasound linear arrays fabricated from micromachined bulk PZT materials - Liu, Changgeng (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2012)
This paper describes the development and characterization of a high-frequency (65-MHz) ultrasound transducer linear array. The array was built from bulk PZT which was etched using an optimized chlorine-based plasma dry-etching process. The median etch rate of 8 µ m/h yielded a good profile (wall) angle (>83°) and a reasonable processing time for etch depths up to 40 μm (which corresponds to a 50-MHz transducer). A backing layer with an acoustic impedance of 6 MRayl and a front-end polymer matching layer yielded a transducer bandwidth of 40%. The major parameters of the transducer have been characterized. The two-way insertion loss and crosstalk between adjacent channels at the center frequency are 26.5 and -25 dB, respectively